Observations on the Prevalence, Characteristics, and Effects of Self-Treatment - Zhao, Yinjun; Ma, Shuangge (Frontiers in Public Health, 2016)
Aims: When facing illness, a person may choose self-treatment as an alternative to hospital (and primary care)-based treatment. Despite its important role in healthcare, the study on self-treatment remains limited. The goal is to collectively report the observations in the literature on the prevalence, characteristics, and effects of self-treatment. Methods: Extensive literature search was conducted, and relevant information was extracted. Results: Published studies have reported that in some regions, the prevalence of self-treatment is high and varies across illness conditions and treatment approaches. Self-medication is the most popular self-treatment approach. Multiple regional, demographic, personal, cultural and religious factors have been implicated in the pursuit of self-treatment. In addition, accessibility of healthcare also plays a role. Self-treatment in general has a positive clinical and financial effect. However there have been concerns on abuse and possible negative effects. Conclusions: This article reviews observations made in recent studies on several important aspects of self-treatment. Comprehensive and systematic study is still lacking. Interventions are needed to solve several problems associated with self-treatment.